2023
DOI: 10.1002/mds.29453
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Cerebellar Transcranial Direct Current Stimulation Reduces Motor and Cognitive Symptoms in Friedreich's Ataxia: A Randomized, Sham‐Controlled Trial

Abstract: BackgroundFriedreich Ataxia is the most common recessive ataxia with only one therapeutic drug approved solely in the United States.ObjectiveThe aim of this work was to investigate whether anodal cerebellar transcranial direct current stimulation (ctDCS) reduces ataxic and cognitive symptoms in individuals with Friedreich's ataxia (FRDA) and to assess the effects of ctDCS on the activity of the secondary somatosensory (SII) cortex.MethodsWe performed a single‐blind, randomized, sham‐controlled, crossover trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
(149 reference statements)
0
2
0
Order By: Relevance
“…The general rule of anodal being excitatory and cathodal inhibitory is probably an oversimplification of the physiological mechanisms underlying tDCS, as numerous factors can turn facilitatory changes into inhibitory, and vice versa. 21 However, although we did not measure cerebellar-brain inhibition to prove our hypothesis, many studies have demonstrated that anodal tDCS increases the inhibitory action of the cerebellum to M1, 23-26 while the dual tDCS effect over the cerebellum has also been confirmed by behavioural studies. 52 We do not believe that the paradoxical response could be attributed to cerebellar atrophy because only two patients had reduced cerebellar volume and these patients’ results were in line with the trend of the whole group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The general rule of anodal being excitatory and cathodal inhibitory is probably an oversimplification of the physiological mechanisms underlying tDCS, as numerous factors can turn facilitatory changes into inhibitory, and vice versa. 21 However, although we did not measure cerebellar-brain inhibition to prove our hypothesis, many studies have demonstrated that anodal tDCS increases the inhibitory action of the cerebellum to M1, 23-26 while the dual tDCS effect over the cerebellum has also been confirmed by behavioural studies. 52 We do not believe that the paradoxical response could be attributed to cerebellar atrophy because only two patients had reduced cerebellar volume and these patients’ results were in line with the trend of the whole group.…”
Section: Discussionmentioning
confidence: 80%
“… 19 Although the tDCS effect is not always predictable, as it also depends on the orientation of the underlying neurons and the sensitivity of their compartments to exogenous current, 20 previous studies have shown that cerebellar tDCS can modulate, in a polarity-specific fashion, the excitability of cerebellar cortical neurons and, consequently, the output from cerebellar nuclei to the motor cortex 17 , 21 , 22 ; more specifically, it has been observed that anodal tDCS increases the inhibitory action of the cerebellum to the motor cortex. 23-26 …”
Section: Introductionmentioning
confidence: 99%